Obstacles to Women's Empowerment in the Kingdom of Saudi Arabia (The International Journal for Scientific Research, 2023)
There is no doubt that the Kingdom of Saudi Arabia has been long overdue towards empowering Saudi women from their political rights, and this is due to the culture of society, which has had a negative impact towards delaying women's enjoyment of their political rights.It is worth noting that Saudi women began to participate in political and public life in general at the official and informal level through their membership in the Shura Council. On September 25, 2011, the King of Saudi Arabia, Abdullah bin Abdulaziz announced the approval of the participation of women in the membership of the Shura Council and municipal councils as a candidate and a vote. As a minimum, 20% of the Shura Council seats are reserved for women.The Kingdom's regulations do not include provisions that prevent women from occupying any of the higher positions, which confirms that there are no legal obstacles towards empowering women, and perhaps the recent amendment of legislation has had an impact in changing the culture of society towards empowering women.The study analyzes the legal impediments to women's exercise of their political rights, as the researcher relied on the descriptive approach that is based on the study of legal texts and internal regulations that dealt with women's political rights at the domestic level, reaching a result that seeks to challenge the most important obstacles to empowering women with all the political rights imposed on them by legislation and regulations Interior of the Kingdom of Saudi Arabia.It is worth noting that the Kingdom's Vision 2030 affirms the political empowerment of the many rights it carried to women and the protection that affirms respect and codification of women's political rights in the Kingdom of Saudi Arabia.The first chapter reviews the political rights established for Saudi women in accordance with the legislation in the Kingdom of Saudi Arabia, and the second chapter deals with the reality of Saudi women exercising their political rights in the Kingdom of Saudi Arabia and deals with obstacles to Saudi women empowering their political rights in the Kingdom of Saudi Arabia.
Keywords: Women; Empowerment; Obstacles